2020
DOI: 10.1155/2020/6279795
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Acephalic Spermatozoa: The Complexity of Intracytoplasmic Sperm Injection Outcomes

Abstract: This review analyses the genetic mechanisms of acephalic spermatozoa (AS) defects, which are associated with primary infertility in men. Several target genes of headless sperms have been identified but intracytoplasmic sperm injection (ICSI) outcomes are complex. Based on electron microscopic observations, broken points of the sperm neck are AS defects that are based on various genes that can be classified into three subtypes: HOOK1, SUN5, and PMFBP1 genes of subtype II; TSGA10 and BRDT genes of subgroup III, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
(128 reference statements)
1
30
0
2
Order By: Relevance
“…One of the unique features of the spermiogenesis is that the Pc moves into the implantation fossa (also recognized as a normal lodging site for the Pc) 30 , 45 , and some proteins may facilitate its attachment to the caudal end of the nucleus. SUN5 directly binds to CENTLEIN, a somatic centrosome protein localized at the proximal ends of the centrioles, but not the centriole distal lumen protein CETN2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of the unique features of the spermiogenesis is that the Pc moves into the implantation fossa (also recognized as a normal lodging site for the Pc) 30 , 45 , and some proteins may facilitate its attachment to the caudal end of the nucleus. SUN5 directly binds to CENTLEIN, a somatic centrosome protein localized at the proximal ends of the centrioles, but not the centriole distal lumen protein CETN2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If centrioles fail to establish physical contact with the nucleus, the sperm head and tail develop independently and separate at spermiation through the seminiferous tubules 13 . Loose sperm heads were infrequent in our study, likely because they are usually phagocytosed by Sertoli cells 12,13 . The distal centriole alone is sufficient to grow a complete flagellum, maintaining progressive motility in the ejaculate 14,15 .…”
Section: Discussionmentioning
confidence: 69%
“…The HTCA originates from the centrosome and connects the nuclear envelope to the intermediate piece of the flagellum [ 26 ]. SUN5 deficiency is associated with a normal assembly of the HTCA during the early stages of spermiogenesis, but it dissociates from the nuclear envelope in elongated spermatids, causing the detachment of the tail from the head [ 27 ]. The ultrastructural analysis of ejaculated spermatozoa from subject P0504 carrying the identified variant also showed that the HTCA was normally assembled but completely detached from the sperm nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%